One‐year clinical results of the NANO registry: A multicenter, prospective all‐comers registry study in patients receiving implantation of a polymer‐free sirolimus‐eluting stent. (21st January 2020) - Liu, Yi; Zhang, Yaojun; Li, Yue; Qi, Tianjun; Pan, Defeng; Wang, Haichang; Liu, Changhui; Ma, Dengfeng; Fang, Zhenfei; Zhang, Ruining; Mou, Fangjun; Tao, Ling; et al.
Abstract: Objectives: We aimed to evaluate the safety and efficacy of Nano+™ (Lepu Medical, Beijing, China) stent implantation in all‐comer patients at the 1‐year follow‐up. Background: The Nano+™ stent is a novel polymer‐free sirolimus‐eluting stent polymer that employs nanoporous stent surface technology to control drug‐delivery. The Nano+™ stent is one of the most widely used drug‐eluting stent (DES) in China. Methods: A total of 2, 481 consecutive patients were included in the multicenter and prospective NANO registry. In this study, the primary endpoint was target lesion failure (TLF) at 1‐year follow‐up, defined as a composite of cardiac death, target vessel nonfatal myocardial infarction (TV‐MI), and clinically driven target lesion revascularization (TLR). The safety endpoint was the occurrence of definite or probable stent thrombosis (ST). Results: Up to 40.2% of patients presented with acute myocardial infarction (AMI). A total of 63.9% of the 2, 904 lesions were American College of Cardiology/American Heart Association (ACC/AHA) type B2 or C lesions. One‐year follow‐up data were available for 98.4% of patients. The 1‐year rate of TLF was 3.1% with rates of 1.3, 1.8, and 0.4% for clinically driven TLR, cardiac death, and TV‐MI, respectively. ST occurred in 0.4% of patients. Diabetes mellitus, AMI, left ventricular ejection fraction <40% and long lesions (>40 mm) were independent predictors of 1‐year TLF. Conclusions: The 1‐year clinical outcomes were excellent for Nano+™ polymer‐free SES implantation in an all‐comer patient population. Follow‐up will be extended up to 5 years, to further elucidate the potential long‐term clinical benefits. Clinical Trial Registration: URL: https://www.clinicaltrials.gov/ . Unique identifier: NCT02929030.